Structure-based virtual screening to identify the beta-lactamase CTX-M-9 inhibitors: An in silico effort to overcome antibiotic resistance in E. coli. (April 2017) - Davari, Kambiz; Nowroozi, Jamileh; Hosseini, Farzaneh; Sepahy, Abbas Akhavan; Mirzaie, Sako
Graphical abstract: Highlights: The new potent inhibitor against beta lactamase CTX-M-9 is introduced by virtual screening. The inhibition mechanism of designed inhibitor (ZINC33264777 ) is proposed. Molecular dynamics studies revealed that in the compound 1: beta lactamase complex, the flexibility of Ω-loop was restricted. Based on ADME studies, all the computed pharmacokinetic parameters ofZINC33264777 are within the reasonable range defined for human use. Abstract: Recently, the quick spreads of broad-spectrum beta-lactams antibiotic resistance in pathogenic strains of bacteria have become a major global health problem. These new emerging resistances cause ineffectiveness of antibiotics and increasing the severity of diseases and treatment costs. Among different and diverse resistance targets, we chose a class A beta lactamase, CTX-M-9, with the aim of identifying new chemical entities to be used for further rational drug design. Based on this purpose, a set of 5000 molecules from the Zinc database have been screened by docking experiments using AutoDock Vina software. The best ranked compound, with respect of the previously proved inhibitor compound19, was further tested by molecular dynamics (MD) simulation. Our molecular modeling analysis demonstrates thatZINC33264777 has ideal characteristics a potent beta lactamase CTX-M-9 inhibitor. In the free form of beta lactamase, NMR relaxation studies showed the extensive motions near the active site and in the Ω-loop. However, our molecular dynamics studies revealed that in the compound 1: beta lactamase complex, the flexibility of Ω-loop was restricted.